COMPARISON OF TIMBAL LEVELS (Pb) ON BLOOD SHELLS (Anadara granosa) AND BAKAU (Shell Telescopium telescopium) IN PLACE AUCTION OF FISH (TPI) LAPPA SINJAI DISTRICT - Rahmawati Rahmawati; Wa Ode Rustiah; Nurhidayat Nurhidayat; Novie Rezkiyana Dewi (Politeknik Kesehatan Makassar, 2020)
Shellfish is one of the sea products that is very popular with the community including the community in Sinjai Regency as a potential coastal and fishery resources that have a fish auction place (TPI). Shellfish are one of the most efficient marine animals to accumulate heavy metals. This is due to the fact that shellfish live in the bottom sedimentary layer of water, move very slowly, and their food comes from detritus in the bottom waters, so the chance of entering heavy metals into the body is very large. Shells can be contaminated by lead (Pb) which enters the body of water through the crystallization of lead in the air with the help of rain water. Lead which accumulates in water and sediments will enter the water and accumulate in the water causing toxic effects on the organisms in it, including some types of shellfish. If humans consume shells that contain heavy metals in high enough quantities will have a negative impact on health. In the human body, heavy metals will combine with active enzymes to become inactive enzymes, so the synthesis of red blood grains (Hb) can be inhibited, consequently it can cause anemia. The purpose of the study was to determine lead content (Pb) in the sample of shellfish. The object of research is blood shells and mangrove shells, analyzed using the Atomic Absorption Spectrophotometer (SSA) method with a total sample of 10. The results obtained by lead (Pb) in blood shells (Anadara granosa) with an average of 0.0439 mg / kg while the mangrove shells (Telescopium telescopium) with an average of 0.0176 mg / kg. Both shellfish samples did not exceed the maximum limit set by the Indonesian National Standard (SNI) of 1.5 mg / kg. Based on the data analysis test p value = 0.011 <0.05 which can be concluded that there is a significant difference between the levels of lead (Pb) in blood shells (Anadara granosa) and mangrove shells (Telescopium telescopium). Keywords: Blood Shells (Anadara granosa), Mangrove Shells (Telescopium telescopium), Lead (Pb), Atomic Absorption Spectrophotometer (SSA)